The geology and vertebrate paleontology of Calvert Cliffs, Maryland - Godfrey, Stephen J.; Smithsonian Institution Scholarly Press (Washington, D.C. : Smithsonian Institution Scholarly Press, 2018)
The last comprehensive review of the fossil vertebrates from the Miocene of Calvert Cliffs was published more than 100 years ago. This volume is a collection of papers that updates some of the geological features of Calvert Cliffs and provides reviews of the fossil biota that includes representatives from the following taxonomic groups: chondrichthyans (chimaeras, shark, skates, and rays), actinopterygians (ray-finned fishes), crocodilians (crocodiles), pinnipeds (seals), and sirenians (sea cows). Peter Vogt, Ralph R. Eshelman, and Stephen J. Godfrey document how the 20-40 m (65-130 feet) high Calvert Cliffs along the Western Shore of Chesapeake Bay continue to yield insights into 18-8 Ma (middle Miocene) geology, marine and terrestrial vertebrate fauna, and origin and evolution of Chesapeake Bay and Calvert Cliffs up to the present. These exposures rank high among the best-known fossiliferous deposits of any age. Bretton W. Kent describes the cartilaginous fish (the chondrichthyan) fauna consisting of 53 species; three chimaeras (ratfishes), 38 sharks, and 12 skates and rays; a fauna rich in large macrophagous sharks and large neritic rays. Giorgio Carnevale and Stephen J. Godfrey present an account of the 38 actinopterygian taxa known from osteological remains and a diverse otolith assemblage of at least 55 taxa. These actinopterygians show an affinity for well-oxygenated muddy and sandy substrates dominated by shallow water species characteristic of the inner shelf, and secondarily by epipelagic taxa. Robert E. Weems details the crocodilians referable to the tomistomine Thecachampsa. The closest living relative is Tomistoma schlegelii, the false-gharial of Southeast Asia. Two species are present: Thecachampsa sericodon and T. antiquus--Provided by publisher.
Includes bibliographical references and index.
Keywords: Geology, Stratigraphic -- Miocene; Geology -- Maryland -- Calvert Cliffs; Paleontology -- Miocene; Paleontology -- Maryland -- Calvert Cliffs; Vertebrates, Fossil; Biology -- Classification